Victims as offenders : the paradox of women's violence in relationships - Miller, Susan L. (Rutgers University Press, 2005)
Are women finally closing the gender gap on violence? Or does this phenomenon reflect a backlash shaped by men who batter? How do abusive men use the criminal justice system to increase control over their wives? Do police, courts, and treatment providers support aggressive arrest policies for women? Are these women "victims" or "offenders"? In answering these questions, Miller draws on extensive data from a study of police behavior in the field, interviews with criminal justice professionals and social service providers, and participant observation of female offender programs. She offers a critical analysis of the theoretical assumptions framing the study of violence and provides insight into the often contradictory implications of the mandatory and pro-arrest policies enacted in the 1980s and 1990s. Miller argues that these enforcement strategies, designed to protect women, have often victimized women in different ways. Without sensationalizing, Miller unveils a reality that looks very different from what current statistics on domestic violence imply.
Keywords: Family violence.; Victims of family violence.; Abused women.; Female offenders.; Battered Women; Victimes de violence familiale.; Femmes victimes de violence.; Criminelles.; Violence familiale.; FAMILY & RELATIONSHIPS -- Abuse -- Elder Abuse.; FAMILY & RELATIONSHIPS -- Abuse -- Domestic Partner Abuse.; SOCIAL SCIENCE -- Sociology -- General.; Abused women; Family violence; Female offenders; Victims of family violence; Gewaltdelikt; Geschlechtsunterschied; Häusliche Gewalt; Frau; Domestic violence; Police and domestic violence; Criminal justice system analysis; Victims; Violent women